Dual spectrometer system with spectral compounding for 1-μm optical coherence tomography in vivo - Cui, Dongyao (2015)
1 μm axial resolution spectral domain optical coherence tomography (OCT) is demonstrated for in vivo cellular resolution imaging. Output of two superluminescent diode sources is combined to provide near infrared illumination from 755 to 1105 nm. The spectral interference is detected using two spectrometers based on a Si camera and an InGaAs camera, respectively. Spectra from the two spectrometers are combined to achieve an axial resolution of 1.27 μm in air. Imaging was conducted on zebra fish larvae to visualize cellular details.